Microencapsulação de Bifidobacterium BB-12 por gelificação iônica interna: estudo da produção, caracterização e viabilidade - Holkem, Augusto Tasch (2016)
The benefits provided by probiotics to the human body have provided their addition to various products, spreading their consumption. However, due to various factors such as storage at low temperatures, acidity and the passage through the human gastrointestinal tract undermine the viability of these organisms. Microencapsulation is alternative for the protection of these probiotics to the human intestine. The aim of this study was to develop probiotic microcapsules Bifidobacterium BB-12 by internal ionic gelation in the wet and freeze-dried form. Moreover, it was analyzed the survival of probiotics under simulated gastrointestinal conditions, tolerance "in vitro" when inoculated at different pH solutions (4.5, 6.0 and 7.5) and viability during storage at different temperatures (-18, 7, 25 °C) at different times for 120 days. In addition to the morphology, mean diameter and physicochemical characterization of microparticles. Under the conditions of 1.5% sodium alginate, 190 ×g rotation speed and 1.5% emulsifier, the microparticles had a mean diameter of 55 μm and an encapsulation yield greater than 90%. In relation to tests simulating gastrointestinal conditions, both the moist microcapsules as lyophilized were resistant, with microbial counts of 12.93 and 11.13 log CFU g-1 respectively, and these are within the standards required by Brazilian law to occur benefits exercised by probiotics. Both moist microcapsules as lyophilized showed good protection in acidic solution (pH 4.5) and total liberation of probiotics in weakly basic solution (pH 7.5). The viability of wet microcapsules was maintained for 75 days at room temperature, and there was a reduction of 6.74 log CFU g-1 over existing storage due to metabolic activity, thus resulting in cell death and loss of cell viability. Compared to other storage temperatures, the refrigeration temperature was further reduction, which was 10.52 log CFU g-1. While, in the freezing showed the best results with a probiotic viability of 7.31 log UFC g-1 after the 120 days. Analyzing the lyophilized microcapsules at room temperature caused a probiotic viability by 60 days. However, refrigeration temperatures and freeze resulted in viable microparticles for 120 days of storage. The results of the physico-chemical characterization indicated encapsulation yield and stability of the microparticles with high efficiency, to facilitate incorporation into food products.